Protoplanetary disc truncation mechanisms in stellar clusters: comparing external photoevaporation and tidal encounters. Issue 2 (19th April 2018) - Winter, A J; Clarke, C J; Rosotti, G; Ih, J; Facchini, S; Haworth, T J
ABSTRACT: Most stars form and spend their early life in regions of enhanced stellar density. Therefore, the evolution of protoplanetary discs (PPDs) hosted by such stars are subject to the influence of other members of the cluster. Physically, PPDs might be truncated either by photoevaporation due to ultraviolet flux from massive stars, or tidal truncation due to close stellar encounters. Here we aim to compare the two effects in real cluster environments. In this vein we first review the properties of well-studied stellar clusters with a focus on stellar number density, which largely dictates the degree of tidal truncation, and far-ultraviolet (FUV) flux, which is indicative of the rate of external photoevaporation. We then review the theoretical PPD truncation radius due to an arbitrary encounter, additionally taking into account the role of eccentric encounters that play a role in hot clusters with a 1D velocity dispersion σ v ≳ 2 km s −1 . Our treatment is then applied statistically to varying local environments to establish a canonical threshold for the local stellar density ( n c ≳ 10 4 pc −3 ) for which encounters can play a significant role in shaping the distribution of PPD radii over a time-scale ∼3 Myr. By combining theoretical mass-loss rates due to FUV flux with viscous spreading in a PPD, we establish a similar threshold for which a massive disc is completely destroyed by external photoevaporation. Comparing these thresholds in local clusters, we find that if either mechanism has a significant impact on the PPD population then photoevaporation is always the dominating influence.